Pendekatan Fenomenologi dalam Resolusi Konflik: Memahami Akar Konflik dengan Mendalam dan Komprehensif - Sidik Puryanto; Ary Purwantiningsih (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This paper discusses the phenomenological approach in the context of conflict resolution. Phenomenology transforms the traditional view of conflict by delving into a profound understanding of its roots, values, emotions, and the perspectives of individuals involved. In this approach, conflict is seen as a social phenomenon involving individual or group awareness, empathy, sympathy, and collective consciousness. The importance of understanding subjective meanings and individual experiences in conflict is emphasized as the key to effective conflict resolution. The conflict resolution process from a phenomenological perspective involves steps of identification, diagnosis, and treatment designed to uncover and comprehend the conflict's roots comprehensively. The role of the subjects in this process is crucial, as they must possess the ability to empathize, see from various perspectives, and facilitate effective communication. In conflict resolution methods based on the phenomenological approach, reduction also becomes a key element, involving efforts to cleanse understanding from biases and assumptions before taking action. Introspection is also vital, helping subjects become more aware of their roles and contributions in the conflict. The phenomenological approach enables us to resolve conflicts in a more profound, holistic, and sustainable manner. With a deeper understanding of conflict's roots and the emotions involved, we can develop more effective solutions and integrate various perspectives contributing to the conflict.